Living Qur'an in the Rateb Siribee Tradition for the Rehabilitation of Narcotics Addicts in Meulaboh - Nafis, Muhammad Wildan; Nurullah, N (QiST: Journal of Quran and Tafseer Studies, 2025)
This study examines the function of the Rateb Siribee tradition as a spiritual rehabilitation model for former drug addicts in Aceh, addressing the limitations of conventional recovery programs that primarily emphasize medical and psychological treatment. Although formal rehabilitation initiatives have been widely implemented, many former users continue to experience social stigma, emotional distress, and susceptibility to relapse upon reentering their communities. Existing research has largely focused on medical and psychological interventions, while studies investigating local spiritual traditions particularly Rateb Siribee as a structured rehabilitation model remain scarce. Scholarship on Rateb Siribee itself predominantly highlights its theological and socio-cultural dimensions, leaving a clear gap regarding its relevance to addiction recovery. To address this gap, the present study aims to: (1) identify the underlying reasons for utilizing Rateb Siribee as a rehabilitation medium; (2) describe its ritual implementation among former addicts; and (3) analyze the spiritual, psychological, and social meanings constructed by participants through their engagement in this tradition. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving religious leaders, mentors, and former addicts in Meulaboh. The findings reveal that Rateb Siribee supports a holistic recovery process through three interrelated forms of meaning-making: strengthening spiritual awareness inspired by QS. Ar-Ra'd: 28; enhancing psychological resilience by improving emotional regulation and reducing anxiety; and fostering social reintegration through acceptance within the dhikr community. Collectively, these experiences cultivate motivation, self-discipline, and a renewed sense of belonging. The study concludes that Rateb Siribee offers a culturally rooted and humanistic rehabilitation model that complements existing approaches and contributes to the development of Islamic-based recovery strategies in Aceh.